Ostatnia zmiana edukacyjna w Finlandii – jej zakres i nauczanie wielostronnej alfabetyzacji - Suwalska, Arleta (Studia Edukacyjne, 2021)
This article reveals the educational change in Finland in the context of multiliteracy. Multiliteracy is one of the seven transversal competences introduced by the Finnish basic education curriculum reform between the years 2012 and 2016. School multiliteracy is developed through cross-subject studies with the usage of particular language. There are involved various texts during teaching to prepare well-educated global citizens who are able to to overcome obstacles of the contemporary world and to follow the global changes in a job market. Multiliteracy helps prepare a global citizen with the skills of global lingua franca.